Les Particules élémentaires: Self–portrait - Gerald Prince (Studies in 20th & 21st Century Literature, 2012)
Perhaps no French novel in the past fifteen years has received more critical attention than Michel Houellebecq’s Les Particules élémentaires and perhaps none has evoked stronger reactions with regard to the (literary) values it espouses and represents. This (self-)portrait, like any portrait, accents certain features more than others. It concentrates on refuting charges of nihilism, reactionaryism, sexism, and racism; it stresses Houellebecq’s novel’s attention to form and its thematic clarity as well as its determination to say something rather than nothing; and, through a consideration of its references to various media, arts, and texts, of its pet peeves and true delights, it specifies the nature and ambition of Les Particules élémentaires, the kind of text it is or aspires to be.
Keywords: novel; self-portrait; nihilism; reactionarism; sexism; racism; Les Particules élémentaires; Michel Houellebecq